2017
DOI: 10.21276/ijee.2017.10.0233
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Heavy Metal Fluxes in Groundwater of Semi-Urban and Urban Settings of Nalagarh Tehsil of Solan District, Himachal Pradesh, India

Abstract: 02-0.068, 0-0.0035, 0.013-0.139, 0.002-0.06, 0.001-0.09, 0.003-0.08, 0.075-0.488, 0,001-0.389

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Heavy metal contamination in the aquatic system is the major threat and main concern of our rivers. Urbanization leads to degradation of our water resources by adding many harmful heavy metals in it (Aiyesanmi et al, 2004;Amajor, 1986;Gupta et al, 2009;Haritash et al, 2008;Khawaja et al, 2017;Rout et al, 2017;Sharma and Walia, 2016). Both natural and anthropogenic activities are responsible for abundance of heavy metals in the environment (Wilson and Pyatt, 2007;Khan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metal contamination in the aquatic system is the major threat and main concern of our rivers. Urbanization leads to degradation of our water resources by adding many harmful heavy metals in it (Aiyesanmi et al, 2004;Amajor, 1986;Gupta et al, 2009;Haritash et al, 2008;Khawaja et al, 2017;Rout et al, 2017;Sharma and Walia, 2016). Both natural and anthropogenic activities are responsible for abundance of heavy metals in the environment (Wilson and Pyatt, 2007;Khan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The groundwater quality studies reveals that water is suitable for drinking, agricultural and industrial purposes if certain water quality/computed parameters found within the desired limits. Many studies on quality of ground and surface water sources on [18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37]. Although many studies have been conducted on suitability of groundwater for domestic needs, however, no extensive study has been done on suitability of water for irrigation purposes with respect to residual sodium carbonate (RSC) in Solan district of the hilly state Himachal Pradesh.…”
Section: Introductionmentioning
confidence: 99%
“…[1]. Many studies on quality of ground and surface water sources on drinking water standards have been carried out by several researchers [2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20]. Although many studies have been conducted on suitability of groundwater for domestic needs, however, no extensive study has been done on suitability of water for irrigation purposes in Solan district of the hilly state Himachal Pradesh.…”
Section: Introductionmentioning
confidence: 99%